2019
DOI: 10.1002/ece3.5886
|View full text |Cite
|
Sign up to set email alerts
|

The influence of experimentally induced polyploidy on the relationships between endopolyploidy and plant function in Arabidopsis thaliana

Abstract: Whole genome duplication, leading to polyploidy and endopolyploidy, occurs in all domains and kingdoms and is especially prevalent in vascular plants. Both polyploidy and endopolyploidy increase cell size, but it is unclear whether both processes have similar effects on plant morphology and function, or whether polyploidy influences the magnitude of endopolyploidy. To address these gaps in knowledge, fifty-five geographically separated diploid accessions of Arabidopsis thaliana that span a gradient of endopoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…In this perspective, endoreduplication in basal salt gland cells could be related with enhanced xenobiotic storage/metabolization potentials (in addition to evolutionary benefits potentially raised by polyploidy), as proposed concerning Arabidopsis trichomes or pavement cells. To date, the relationship between inherited polyploidy and endopolyploidy is still unclear, but Pacey et al. (2020) provided recent evidences that polyploidy reduces endopolyploidy (by comparing Arabidopsis diploid vs. colchicine-treated tetraploid accessions).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this perspective, endoreduplication in basal salt gland cells could be related with enhanced xenobiotic storage/metabolization potentials (in addition to evolutionary benefits potentially raised by polyploidy), as proposed concerning Arabidopsis trichomes or pavement cells. To date, the relationship between inherited polyploidy and endopolyploidy is still unclear, but Pacey et al. (2020) provided recent evidences that polyploidy reduces endopolyploidy (by comparing Arabidopsis diploid vs. colchicine-treated tetraploid accessions).…”
Section: Resultsmentioning
confidence: 99%
“…In this perspective, endoreduplication in basal salt gland cells could be related with enhanced xenobiotic storage/metabolization potentials (in addition to evolutionary benefits potentially raised by polyploidy), as proposed concerning Arabidopsis trichomes or pavement cells. To date, the relationship between inherited polyploidy and endopolyploidy is still unclear, but Pacey et al (2020) provided recent evidences that polyploidy reduces endopolyploidy (by comparing Arabidopsis diploid vs. colchicine-treated tetraploid accessions). However, such trade-off was not currently reported between all Arabidopsis genotypes considered by Scholes (2020), depicting that endopolyploidy affected by inherited polyploidy is genotype dependent, and may also increase specifically in tetraploid plants in response to stress damage.…”
Section: The Putative Advantages Of Endopolyploidy In Specialized Celmentioning
confidence: 99%
“…It is possible that our data underestimated organellar genome copy numbers per cell if a significant fraction of the leaf cells have experienced endoreduplication. Species with large genomes, including polyploids, have been shown to undergo lower rates of endoreduplication (Barow and Meister, 2003; Pacey et al ., 2020). Therefore, the difference in the actual average amount of nuclear DNA per cell in diploids vs. polyploids may be lower than implied by their nominal ploidy levels, resulting in a form of immediate compensation in the polyploid species.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, endopolyploidy may simply compensate for low DNA content in gametophytic (haploid) or sporophytic (diploid) tissues and help to promote growth and development through nucleotypic effects. Recent studies of endopolyploidy in diploid and isogenic polyploid angiosperms have revealed that diploids tend to show higher endopolyploidy than autopolyploids [ 41 , 67 ], possibly due to compensation for lower basic inherited organism-specific ploidy. These studies, however, conclude that this pattern is not general but genotype-specific.…”
Section: Discussionmentioning
confidence: 99%